1968
DOI: 10.1097/00004032-196802000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Radioactivity of Brazil Nuts

Abstract: It has been known for some time that Brazil nuts have a high barium content and their natural radioactivity is the highest among foodstuff grown in areas of normal radiation background.Samples of Brazil nuts of known origin, as well as various parts of their trees, were obtained from different regions of the Amazon valley and analyzed for barium, calcium, 226Ra, 228Ra and total alpha activity.No statistically significant correlation was found between concentrations of calcium and barium in the nuts. In general… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
8
0

Year Published

1990
1990
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 1 publication
2
8
0
Order By: Relevance
“…The 226 Ra concentrations (17-31 mBq/g) in the nuts span a factor of two range, and are higher than concentrations that have been measured (Eisenbud, 1997) in grains and vegetables (o0.1 mBq/g). For a given nutmeat, the isotopic concentrations of 226 Ra and of 228 Ra are comparable, and in agreement with results from different localities of Brazil (Penna-Franca et al, 1968). While there was no decay correction required for 226 Ra and 228 Ra, the status of radioactive equilibrium for 224 Ra (T 1/2 ¼ 3.7 d) could not be assessed in the samples, and no decay correction could justifiably be applied.…”
Section: Ra In Brazil Nutssupporting
confidence: 83%
See 1 more Smart Citation
“…The 226 Ra concentrations (17-31 mBq/g) in the nuts span a factor of two range, and are higher than concentrations that have been measured (Eisenbud, 1997) in grains and vegetables (o0.1 mBq/g). For a given nutmeat, the isotopic concentrations of 226 Ra and of 228 Ra are comparable, and in agreement with results from different localities of Brazil (Penna-Franca et al, 1968). While there was no decay correction required for 226 Ra and 228 Ra, the status of radioactive equilibrium for 224 Ra (T 1/2 ¼ 3.7 d) could not be assessed in the samples, and no decay correction could justifiably be applied.…”
Section: Ra In Brazil Nutssupporting
confidence: 83%
“…proteins) of the nut. In addition to Se, Brazil nuts are reported (Penna-Franca et al, 1968) to accumulate significant concentrations of barium (Ba) and radium (Ra). Therefore, Brazil nuts reportedly contain elevated levels of beneficial (Se) and potentially toxic (Ba) elements, as well as a Class A carcinogen (Ra).…”
Section: Introductionmentioning
confidence: 99%
“…The presence of radium isotopes in Brazil nuts is known for a long time from pioneering works. Even some observations were made on the possibilities of people who consume a considerable amount of the nuts, during many years, building up elevated radium body burdens (Penna-Franca et al, 1968). The mean of AC for K-40 in Brazil nut found by Armelin (2016) was (225 ± 59) Bq/kg.…”
Section: Resultsmentioning
confidence: 99%
“…The study showed that of all the food items measured, Brazil nuts were the most active (9). According to Penna-Franca et al, the Brazil nut tree has an extensive root system with an unusual affinity to absorb and concentrate barium (10). In the process of absorbing nutrients from the soil, it also absorbs and concentrates 226 Ra and 228 Ra.…”
mentioning
confidence: 95%
“…In the process of absorbing nutrients from the soil, it also absorbs and concentrates 226 Ra and 228 Ra. This happens because radium and barium have similar chemical behavior (10). Our goal was to see if raw Brazil nuts purchased from a local supermarket would give us any readings above background level.…”
mentioning
confidence: 99%